An Evaluation of The Legal Mechanisms Put in Place to Protect the Rights of Women with Special Needs in Cameroon - Tangwa Modestine Ginje (Zien Journals, 2021)
Over the past years, protection of the rights of the vulnerable such as women with special needs has been the concern of most international human rights treaties and institutions. In 2008, the UN adopted the Convention on the Rights of Persons with Disability; mandating state parties to take positive measures to ensure proper and effective protection of the rights of the PWDs including women. Cameroon being a party to this treaty hided to the call of the UN put in place legal measures for effective enforcement of the rights of these persons. One of the most important law put in place was the 2010 law protecting this category of persons in Cameroon. Despite the measures taken by the state of Cameroon, it is found that women with special needs still face gross violation of their rights which is a major criticism to the measures taken.
Keywords: Women with special needs; vulnerable; Disability; Protection; Rights